United States’ Africa Command and Maritime Security in the Gulf of Guinea, 2007 – 2020 - Nnamani, Felix Vincent (Journal of Contemporary International Relations and Diplomacy, 2022)
This study examined the impact of US Africa Command on maritime security in the Gulf of Guinea in West Africa, between 2007 and 2020, with specific emphasis on the core maritime security challenges in West Africa. The study was anchored on the World Systems Theory, while data were generated using documentary and survey methods. Data collected were analysed using content analysis. The study found that maritime security challenges in West Africa include piracy, armed robbery, and drug trafficking. It also found that maritime insecurity has remained endemic in the Gulf of Guinea, despite the establishment of US Africa Command. The study locates the limited effectiveness of AFRICOM in mitigating maritime security challenges to its establishment without adequate consultation with West African leaders which triggered suspicion and resistance among countries in the Gulf of Guinea. The study posits that the geostrategic importance of the sub-regional maritime has remained the U.S government’s strategic interest. The study, therefore, recommends, among others, that the U.S. government should strengthen inter-state collaboration through existing security agencies in the sub-region.